SITUS WOTANNGARE-BOJONEGORO: NILAI PENTING DAN PENGEMBANGANNYA - Hery Priswanto (Balai Arkeologi Yogyakarta, 2013)
Wotanngare site is believed to be the former Kingdom of Malawapati (Mlawatan Site) as well as the palace of King Anglingdarma. By local community, King Anglingdarma is a legendary and heroic figure for Bojonegoro society. This is supported by the toponym, toponyms related to Anglingdarma such as Budhug Village, Tibong Land, Kedhung Gandhu, Pathak Kedhung Buto, and Mount Pegat. Based on the results of the research carried out Balai Arkeologi Yogyakarta, Wotanngare Site in Bojonegoro regency is a settlement site Majapahit period. The archeological as well as the legend significance would be combined to contribute academically to the Bojonegoro community.